2015
DOI: 10.5455/2320-6012.ijrms20150132
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of immediate postpartum intra uterine device insertion in a tertiary level hospital

Abstract: Background: In India there is an unmet need for contraception. Intrauterine device is a long acting reversible method. This study was done to determine the efficacy and safety of immediate Post-Partum Intrauterine Device (PPIUD) and to compare the outcome of PPIUD insertion after vaginal delivery and caesarean section. Methods: A total of 113 women who underwent PPIUD insertion were followed up at 6 weeks and 6 months postpartum. Outcome in term of side effects, removal and expulsion was compared in vaginal de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 7 publications
2
10
1
Order By: Relevance
“…The excessive discharge in 26.09% women was the most common symptom in the present study as compared to other studies done with Cu T 380 A by Sharma A et al (10) (1.04%). The reason for higher rate of excessive discharge in this study could be due to the reaction caused by nylon thread of Cu 375 in contrast to polyethylene thread of Cu T 380 A used in other studies.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The excessive discharge in 26.09% women was the most common symptom in the present study as compared to other studies done with Cu T 380 A by Sharma A et al (10) (1.04%). The reason for higher rate of excessive discharge in this study could be due to the reaction caused by nylon thread of Cu 375 in contrast to polyethylene thread of Cu T 380 A used in other studies.…”
Section: Discussionsupporting
confidence: 67%
“…The reason for higher rate of excessive discharge in this study could be due to the reaction caused by nylon thread of Cu 375 in contrast to polyethylene thread of Cu T 380 A used in other studies. Only 4.35% women had menorrhagia in the present study which was lower than the study done by Sharma A et al (10) (16.66%) and Kanhere et al (5) (6%). Lower rates of menorrhagia in the present study could be due to coverage of broad spectrum antibiotics and antiinflammatory after the PPIUCD insertion.3 women (2.61%) after 6 months reported pregnancy in the present study; unfortunately the reason could not be explained.…”
Section: Discussioncontrasting
confidence: 55%
“…In another study by Sharma et al, in 59 (61.45%) women there was no complaint regarding PPIUD results being similar to ours. 7 In an another study by Shukla et al using Cu T 200 B in immediate post-partum period, they found it was only 11.3% of participants were symptom less at 6 months. 8 Kittur et al has shown that 86.2% of subjects in their study were satisfied with the PPIUCD insertion.…”
Section: Lall J Et Al Int J Reprod Contracept Obstet Gynecol 2017 Mmentioning
confidence: 94%
“…Sharma etal, in their study compared the outcomes of PPIUCD insertion after vaginal delivery and caesarean section in terms of side effects, removal and expulsion. 13 Therefore, the present study was undertaken to evaluate the safety and efficacy of insertion of post-partum IUCD in women and to compare the outcomes of PPIUCD insertion after vaginal delivery and caesarean section.…”
mentioning
confidence: 99%